Novas fronteiras do trabalho: vivências à margem dos trabalhadores do tráfico de drogas - Oliveira, Juliana e Silva de (2009)
This work aims to bring an understanding about the experiences of workers facing the reality of the jobs of atypical forms of work, according to the wage model, considered in a position beyond the edge of the society. More specifically, we aim to make a survey on drug workers, in relation to their position of marginality, considering the importance of their financial gain. We initiated this study discusses the changes in the capitalist system, from new forces of domination, which brings as a consequence some changes in ways of managing the work, spreading the flexibility and reduction, which in turn has justified the emergence of occupations increasingly atypical of insertion. From the vision of production of subjectivity through social practices, we can see that the restructuring process of production interferes with the formation of workers in the contemporary, governed by the principles of consumption. Based on this context, we tried to investigate the working conditions of employees in the drug trade. We observed that this occupation also follows the logic of capital and it comes in response to economic marginalization, working as an illegal alternative to the mass of workers who can not find a legal insertion. Track this theoretical path, we follow for the conduct of qualitative research with five employees of the drug trade in two neighborhoods of the city of Fortaleza. We conducted semi-directed interviews that were submitted to a semantic analysis of content. The contents were organized into four categories, for teaching purpose only, to facilitate understanding of the data: reasons for insertion and permanence, the meanings attributed to work, organization of work in drug traffic, consumption and limited integration. From the analysis we can say that drug trafficking is a complex category and brings contradictions, as is in a position of marginality, but ends up corresponding, due to gains it provides, to a means of recognition, at least at the level of consumption. However, this inset shows is limited, approximate idea of the concept of marginal insertion of Castel (1998), because workers in such activity still experiencing a marginal situation, before the restriction of social participation of certain groups and against the collective context wider society.